Optimized PVP/CTAB-NiZnS nanostructures served as an efficient dye degrader and antibacterial agent with computational validation - Aftab Ali Saeed, Muhammad; Imran, Muhammad; Haider, Ali; Shahzadi, Anum; Moeen, Sawaira; Ul-Hamid, Anwar; Ullah, Hameed; Abd-Rabboh, Hisham S.M.; Ikram, Muhammad (Journal of molecular structure, 2025)
•Prepared pure and PVP doped into CTAB-NiZnS nanostructure via Co-precipitation.•Capping agent PVP and CTAB controlled the particle size of NiZnS.•6 % PVP/CTAB-NiZnS showed highest degradation (76.36 %) in neutral medium.•Doped Nanostructure revealed 6.05 mm inhibition zone against S. aureus. A co-precipitation strategy was employed to synthesize PVP/CTAB-NiZnS NSs (polyvinylpyrrolidone/cetyltrimethylammonium bromide-nickel zinc sulfide nanostructures) with fixed (4 wt. %) CTAB and varying weight ratios (2 ad 6 wt. %) of PVP. This research aimed to enhance the Rhodamine B reduction and bactericidal activity towards S. aureus using the synthesized NSs, with theoretical validation through molecular docking. CTAB and PVP provide surface modification, structural stability, electron transfer properties, good physiological compatibility, and electron transfer efficacy that increase the dye reduction and bactericidal activity of NiZnS. Comprehensive characterizations were employed to examine the structural, optical properties, vibrational modes, chemical composition, and morphological features of PVP/CTAB-NiZnS. The bandgap energy (Eg) of NiZnS was increased from 3.17 to 3.22 eV with CTAB and PVP addition. The formation of nanowires (NWs) with a few rods of NiZnS was confirmed through TEM analysis. The study findings indicate that the optimized sample (6 % PVP/CTAB-NiZnS) outperformed all other prepared samples, achieving a maximum dye reduction of 76.36 % in a neutral medium within 10 min. Additionally, this highly doped sample displayed bactericidal activity, evidenced by a maximum inhibition zone of 6.05 mm against Staphylococcus aureus. A molecular docking study was conducted to provide theoretical support for the bactericidal activities of PVP/CTAB-doped NiZnS nanostructures against DNA gyrase in S. aureus. The docking studies indicate that these NSs may function as inhibitors of DNA gyrase. [Display omitted]